The Effects of YAP and Its Related Mechanisms in Central Nervous System Diseases - Jin, Jiayan; Zhao, Xiaoxuan; Fu, Huifang; Gao, Yuan (Frontiers in Neuroscience, 2020)
Yes-associated protein (YAP) is a key effector downstream of the Hippo signaling pathway and plays an important role in the development of the physiology and pathology of central nervous system (CNS), especially regulating cell proliferation, differentiation, migration and apoptosis. However, the roles and underling mechanisms of YAP in CNS diseases are still puzzled. Here, this review will systematically and comprehensively summarize the biological feature, pathological role and underlying mechanisms of YAP in normal and pathologic CNS, which aims to provide insights into the potential molecular targets and new therapeutic strategies for of CNS diseases.